Co-infections among COVID-19 adult patients admitted to intensive care units: results from a retrospective study - Damico, V.; Murano, L.; Margosio, V.; Ripamonti, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Co-infection rates increase in patients admitted to the Intensive Care Units. The aim of this study was to examine the Healthcare Associated Infections in critically ill adult patients infected with SARS-CoV-2.Methods. A retrospective observational study in adults with confirmed SARS-CoV-2 infection requiring intensive care unit admission was performed. From February 2020 to September 2021, healthcare records from a total of 118 patients were evaluated.Results. In the study period, 39 patients were diagnosed with at least 1 Healthcare Associated Infection (33.1%). The co-infection/co-colonisation rate >48 hours after admission was 29.0 per 1,000 person/ days (95 % CI 19.1–33.9). A total of 94 isolates were identified, the most common being Klebsiella spp, Clostridium difficile, Acinetobacter baumanii and Enterococcus spp. Associated outcomes for Healthcare Associated Infections have been identified: age >64 years (p= .003), length of Intensive Care Unit stay> 7 days (p= .002), Type 2 Diabetes mellitus (p= .019), cardiovascular disease (p= .021), inserted central venous  catheter (p= .014), intubation (p< .001), APACHE II score >25 (p< .001), mechanical ventilation >48 hours (p= .003),  and inserted urinary catheter (p= .002). The overall fatality rate of patients included in the study was 41.5% (n= 49), and it was found to be significantly higher in patients who acquired a Healthcare Associated Infection (n=26/39, 66.7%) compared to those who did not acquire it (n= 23/79, 29.1%) (OR= 4.87; 95% CI = 2.14-11.10; p< .001).Conclusions. Our study showed high rates of Healthcare Associated Infections in critically ill adults with COVID-19. Associated factors for Healthcare Associated Infections acquisition and fatality in Intensive Care Units patients were identified as a good reason for a revision of existing infection control policies.